Дослідження ефективності методики навчання технічних дисциплін засобами інформаційно-комунікаційних технологій - Тітова, Олена Анатоліївна; Титова, Елена Анатольевна; Titova, Olena (My University, 2010)
UK: В статті наведені результати дослідження ефективності методики навчання технічних дисциплін засобами інформаційно-комунікаційних технологій на основі дисципліни «Трактори і автомобілі». EN: The article deals with the results of new learning methods studying. The new methods refer to the information and communication technologies application for technical subjects learning.
Studying of the efficiency of methods of the information and communication technologies application for technical subjects learning
Keywords: інформаційно-комунікаційні технології; навчальне програмне забезпечення; ефективність навчання; information and communication technologies; teaching software; educational efficiency